Estimation of various associated factors in multiparous females undergoing primary caesarean sections at a tertiary care health centre in rural Western Maharashtra, India - Nene, Deepti Kiran; Baheti, Tushar Chandrakant; Bangal, Vidyadhar B. (International Journal of Research in Medical Sciences, 2020)
Background: Caesarean section is one of the commonly performed operation in women due to safety reason and modern techniques. Primary caesarean section in the multipara means first caesarean section done in the patients who had previously delivered vaginally once or more. Aims and objectives of this study were to know association of various parameters like Age, Parity, Haemoglobin, Blood Pressure, Baby weight, Perinatal and Maternal Mortality with primary caesarean section among multipara. Methods: This was a prospective study of primary caesarean section in multipara women admitted at tertiary care hospital in western rural Maharashtra during the period of 6 months from January 2018 to June 2018. Multipara with pregnancy of >28 weeks gestation (gravida 2 and above), each of whom has had a previous vaginal delivery of >20 weeks gestation were included. Women with previous abortions and previous section were excluded. Results: Total 1705 sections were performed during the same period out of total 4648 deliveries. Out of these sections 194 sections were performed in multipara for the first time. Maximum numbers of patients (58%) were in the age group of 15-24 years and Parity 2 (68%). Almost 70% women among multipara have Hb <11 Mgm/dl. Most of the patients (84.53%) have normal Blood pressure readings. Most of the babies’ i.e.70 (36.08%) have birth weight in the range of 2.5-3 kg. Out of 194 deliveries, there were only 3 neonatal deaths (1.54%) and 1 maternal death (0.51%). Conclusions: Proper antenatal and intrapartum care and early referral can reduce the maternal and perinatal morbidity and mortality in multipara.